The Impact of Private Standards on Corporate Social Responsibility Compliance and Rural Workers’ Motivation in Developing Countries: A Study of Mango Farms in Pakistan - Honglei Tang; Zeeshan Rasool; Ahmad Imran Khan; Anum Afzal Khan; Mohsin Ali Khan; Ghulam Ahmad Azaz (International Journal of Food Science)
This study examines the role of a private standard on corporate social responsibility (CSR) compliance in the Pakistani mango industry and how this compliance affects rural workers’ motivation. Pakistan is the fifth largest mango producer in the world and the fourth largest exporter in global mango trade; also, mango is the biggest fruit crop within the country. Mango trade is subject to trade terms, where buyers decide the conditions of trade agreements by means of codes of conduct. The key dimensions of the codes involved in agrofood trade are food safety, traceability, worker welfare, and environmental consideration, issues which are all connected with CSR. Private standards ensure compliance with these codes of conduct. This study draws on interviews and a questionnaire survey with certified mango producers and farm workers in Pakistan. The mango industry also involves other stakeholders such as government institutes and NGOs; interviews were also conducted with their representatives. Given that this study is an impact assessment research, the researcher designed a theoretical framework using a mixed method approach to investigate the rationale behind acquiring the standard by the mango growers in Pakistan and what impact (if any) this shift has generated with regard to the farm workers’ job satisfaction and motivation. This study is the first to empirically examine good agricultural practices in Pakistan and evaluate their impact. This study shows that private standards play a significant role in ensuring compliance, and CSR practices implemented through them were found to be positively related to the rural workers’ job satisfaction and motivation. Furthermore, this study has made separate contributions to theory, methodology, and practice. The production of the synergistic model for improving compliance is among the key highlights of the study. The findings of this study can extend to other agriculture and primary production industry workers in Pakistan and even beyond to other developing countries’ rural agriculture workers.